A rigidity–flexibility balance strategy enabling highly photoluminescent two-dimensional covalent organic framework nanosheets. Issue 70 (16th August 2022) - Wang, Hao; Gong, Chengtao; Jin, Peng; Guo, Chenglong; Wang, Danfeng; Xu, Guodong; Peng, Yongwu
Abstract : A rigidity–flexibility balance strategy was proposed for constructing highly photoluminescent two-dimensional covalent organic framework nanosheets with an extremely high PLQY (43.5%). Abstract : The fluorescence quenching phenomenon commonly found in two-dimensional COFs is due to either the strong interlayer π–π stacking or the non-radiative decay caused by intramolecular rotation. Here, we report a rigidity–flexibility balance strategy for constructing highly photoluminescent 2D COF nanosheets via the integration of rigid fluorescent molecular nodes with flexible non-planar building blocks. The prepared COF nanosheets, termed TPE-DBC-COF, achieve extremely high PLQY in common organic solvents, especially in tetrahydrofuran (43.5%). Besides, the prepared TPE-DBC-COF exhibits excellent sensitivity and selectivity to tetracycline hydrochloride and high cycling stability, so it can be used as a high-efficiency fluorescent sensor for the detection of tetracycline hydrochloride down to the ppm level.